2018
DOI: 10.1074/jbc.ra118.003187
|View full text |Cite
|
Sign up to set email alerts
|

ATP-binding cassette member B5 (ABCB5) promotes tumor cell invasiveness in human colorectal cancer

Abstract: ABC member B5 (ABCB5) mediates multidrug resistance (MDR) in diverse malignancies and confers clinically relevant 5-fluorouracil resistance to CD133-expressing cancer stem cells in human colorectal cancer (CRC). Because of its recently identified roles in normal stem cell maintenance, we hypothesized that ABCB5 might also serve MDR-independent functions in CRC. Here, in a prospective clinical study of 142 CRC patients, we found that ABCB5 mRNA transcripts previously reported not to be significantly expressed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 55 publications
2
38
1
Order By: Relevance
“…Several factors might be contributing to this differential in vivo response. Our recent discoveries that ABCB5 serves as a critical mediator of receptor tyrosine kinase (RTK) signaling with growth-inducing and anti-apoptotic functions in normal tissues and cancer (35,48) suggest that constitutive activation of this pathway in the setting of PTEN loss in U-87 MG cells can override the effect of ABCB5 blockade. This mechanism might be responsible for the limited impact of ABCB5 blockade on CD133-positive GBM CSC frequency in U-87 MG cells compared to LN-229 and LN-18 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors might be contributing to this differential in vivo response. Our recent discoveries that ABCB5 serves as a critical mediator of receptor tyrosine kinase (RTK) signaling with growth-inducing and anti-apoptotic functions in normal tissues and cancer (35,48) suggest that constitutive activation of this pathway in the setting of PTEN loss in U-87 MG cells can override the effect of ABCB5 blockade. This mechanism might be responsible for the limited impact of ABCB5 blockade on CD133-positive GBM CSC frequency in U-87 MG cells compared to LN-229 and LN-18 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Generation of stable LN-229 and U-87 MG ABCB5 knockdown (KD) or their respective shControl cell variants was accomplished as in (18,48) followed by puromycin selection (2 μg/mL). Reduction of ABCB5 protein expression in ABCB5 KD cell lines was confirmed by immunoprecipitation (IP)-Western blot.…”
Section: Generation Of Stable Abcb5 Knockdown Glioblastoma Cell Variamentioning
confidence: 99%
“…Sommers et al found that two adriamycin‐resistant MCF‐7 cell lines and a vinblastine‐resistant ZR‐75‐B cell line underwent EMT. In a recent study, Guo et al also reported that the MDR‐related protein ATP‐binding cassette member B5 (ABCB5) was associated with EMT, which might regulate the mesenchymal cellular phenotype in CRC cells. In our study, E‐cadherin was found to be down‐regulated, whereas, the expression of ZEB1 and Vimentin was found increased in HCT‐8/5‐FU and SW480/5‐FU cells compared with that in HCT‐8 and SW480 cells, indicating the occurrence of EMT in MDR cells of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…year (Ricci-Vitiani et al, 2007). CD44 as a receptor of hyaluronic acid in extracellular matrix (ECM) (Leng et al, 2018), ATP-binding cassette transporter as a drug efflux pump, which promotes tumor cell resistance to chemotherapies (Guo et al, 2018), CD166 as another adhesion molecule to ECM (Shafaei, Sharbatdaran, Kamrani, & Khafri, 2013) are some other robust surface markers of CCSCs (Table 1). Some of these cell surface markers not only are applied in the identification and isolation but also are used in targeted therapy such as in the case of…”
Section: Colon Cancer Stem Cellsmentioning
confidence: 99%
“…Ricci‐Vitiani et al () showed that subcutaneous injection of CD133− colon cancer cells in immunodeficient mice did not have tumor formation ability, whereas CD133+ cells not only reproduced the original tumor but also they could grow as undifferentiated tumorspheres in serum‐free medium for more than 1 year (Ricci‐Vitiani et al, ). CD44 as a receptor of hyaluronic acid in extracellular matrix (ECM) (Leng et al, ), ATP‐binding cassette transporter as a drug efflux pump, which promotes tumor cell resistance to chemotherapies (Guo et al, ), CD166 as another adhesion molecule to ECM (Shafaei, Sharbatdaran, Kamrani, & Khafri, ) are some other robust surface markers of CCSCs (Table ). Some of these cell surface markers not only are applied in the identification and isolation but also are used in targeted therapy such as in the case of LGR5 directed antibody‐drug conjugates.…”
Section: Introductionmentioning
confidence: 99%